IMPLEMENTASI PENDIDIKAN ISLAM MODERAT DALAM MEMBENTUK KARAKTER RELIGIUS DI PONDOK PESANTREN DARUTHOLIBIN SOTO TUBAN - Shiva Nurul Fitria; Ali Ahmad Yenuri (Journal Multicultural of Islamic Education, 2026)
Education is not only tasked with educating the nation but also building a nation that has a religious character. Seeing many cases related to various kinds of social problems such as moral crises and so on. Of course, this is a big problem for our nation. When discussing morals, of course it is closely related to morals, manners and character. One of the educational institutions that really focuses on these aspects is Islamic boarding schools. Islamic boarding schools are educational institutions that are expected to form a religious character because almost all of the lives of students are regulated by the regulations in Islamic boarding schools. Seeing the many successes of Islamic boarding schools in forming character, of course there are implementations and implications. So this thesis raises the following problems: how is the implementation of moderate Islamic education in forming religious character at the Daruttholibin Soto Islamic boarding school. This research uses a type of case study research with a descriptive-qualitative method, namely research produced with descriptive data in the form of words and written or spoken words from the objects observed. Data collection techniques are carried out through: Observation, Interviews and Documentation. The results of the research show that: The implementation of religious character education that has been implemented at the Darutholibin Islamic boarding school includes congregational prayers, muhadhoroh, familiarization with tahfidz Qur'an, commemorating Islamic and national holidays, giving awards to students who excel, and principles exemplary.